Gladiolus alanyensis (Iridaceae), a new species from southern Turkey in the eastern Mediterranean basin - Sağiroğlu, Mehmet; Tekşen, Mehtap; Duman, Hayri̇; Karaman, Seher; Çakir, Ece Gökçe (Phytotaxa, 2022)
Gladiolus alanyensis is described and illustrated as a new species from Alanya, Antalya Province in South Anatolia, Turkey. In this study, the diagnostic morphological features, distribution, habitat and ecological characteristics, and conservation status of the new species are reported. It grows in calcareous areas and is morphologically close to G. anatolicus. Affinities and differences to other species such as G. triphyllus and G. humilis are also commented. Seed micromorphological characteristics of G. alanyensis, G. anatolicus and G. humilis are examined and compared using LM and SEM analyses.